1996
DOI: 10.1148/radiology.200.2.8685350
|View full text |Cite
|
Sign up to set email alerts
|

Labral injuries: accuracy of detection with unenhanced MR imaging of the shoulder.

Abstract: With appropriate pulse sequences, unenhanced MR imaging of the shoulder is an accurate technique for the detection and localization of labral injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(54 citation statements)
references
References 0 publications
7
43
0
4
Order By: Relevance
“…Type I Type II Type III Type IV MR arthrography No SLAP 28 1 4 1 0 Type I 0 0 1 0 0 Type II 2 3 30 0 1 Type III 0 0 1 1 2 Type IV 0 0 1 1 1 Discussion SLAP lesions are a well-recognized cause of shoulder disability with incidences reported between 5.9% [13] and greater than 10% [8] following shoulder trauma. Direct MR arthrography has been shown to be an effective method for diagnosing SLAP tears [3][4][5]8] and in most studies has proven superior to conventional MR imaging in identifying SLAP lesions [14,15]. In the present study sensitivity, specificity and accuracy in detecting SLAP lesions compared with arthroscopy were within the same range as in previous studies using MR arthrography [3][4][5]8].…”
Section: Superior Glenoid Labral Cysts (Ganglia)supporting
confidence: 81%
“…Type I Type II Type III Type IV MR arthrography No SLAP 28 1 4 1 0 Type I 0 0 1 0 0 Type II 2 3 30 0 1 Type III 0 0 1 1 2 Type IV 0 0 1 1 1 Discussion SLAP lesions are a well-recognized cause of shoulder disability with incidences reported between 5.9% [13] and greater than 10% [8] following shoulder trauma. Direct MR arthrography has been shown to be an effective method for diagnosing SLAP tears [3][4][5]8] and in most studies has proven superior to conventional MR imaging in identifying SLAP lesions [14,15]. In the present study sensitivity, specificity and accuracy in detecting SLAP lesions compared with arthroscopy were within the same range as in previous studies using MR arthrography [3][4][5]8].…”
Section: Superior Glenoid Labral Cysts (Ganglia)supporting
confidence: 81%
“…1 Sensitivities of 100% for anterior labral tears, 86% for superior labral tears and 74% for posterior labral tears as compared with arthroscopy have been reported using high-resolution 1.5 T conventional MR examinations. 2 Sensitivities and specificities for detection of labral tears as compared with those from arthroscopy in the current study compares favourably with previously published studies.…”
Section: Connollysupporting
confidence: 86%
“…1 Sensitivities of 100% for anterior labral tears, 86% for superior labral tears and 74% for posterior labral tears as compared with those from arthroscopy have been reported using high-resolution 1.5 T conventional MR examinations. 2 In our practice, we have been told by our surgeons that we describe some SLAP tears and posterior labral tears on MR that they find on arthroscopy to be degenerative fraying. For this reason, we sought to find (1) how often does a surgeon intervene on labral tears and (2) how do surgeons describe labral tears seen at MR examinations in their arthroscopy reports.…”
mentioning
confidence: 99%
“…3 High sensitivity and specificity for the detection of labral tears at 1.5 T has also been reported. 4,5 A previous study demonstrated higher accuracy with MR arthrography than with conventional MR in a group of professional baseball players. 6 Previous studies have demonstrated MR arthrography to have higher accuracy in the detection of labral tears than conventional MR examination.…”
Section: Introductionmentioning
confidence: 97%
“…This has been postulated to be a result of joint distension and the hyperosmolar contrast injected into the joint. 11 Both Gusmer et al 4 and Hodler et al 12 stated that MR arthrography is an invasive procedure, limiting its wide acceptance. 13 In this study, we sought to determine in which patient population 3-T MR arthrography demonstrates additional clinically relevant findings as compared with conventional 3-T MR. To address this question, we designed this study to look at both conventional MRI and MR arthrography in the same patient population and compare the results with arthroscopy.…”
Section: Introductionmentioning
confidence: 99%